Evaluate the nutritional reaction at winter wheat after different forecrops - Szilágyi, Gergely (Acta Agraria Debreceniensis, 2016)
Our field researches took place on the Látókép test farm of Agricultural Science Centre of University of Debrecen, Centre for Agricultural and Applied Economic Sciences, in long-term experiment, on calcareous chernozem soil, in growing season of 2014/2015. In our experiment we examined the fertilizer reaction and the yield of different winter wheat genotypes (GK Öthalom, GK Csillag, Mv Csárdás, Mv Toldi) with grain maize and sweetcorn forecrops. According to our results, the sweetcorn forecrop strongly affected the yield. In the average of the fertilizer treatments and the varieties, after sweetcorn forecrop 6.9 t ha-1, after grain maize forecrop 5.4 t ha-1 average yield was gained. According to our data, the fertilizer reactions of the varieties were significantly different.